2021
DOI: 10.1002/clc.23551
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and design of the precise percutaneous coronary intervention plan (P3) study: Prospective evaluation of a virtual computed tomography‐based percutaneous intervention planner

Abstract: Introduction Fractional flow reserve (FFR) measured after percutaneous coronary intervention (PCI) has been identified as a surrogate marker for vessel related adverse events. FFR can be derived from standard coronary computed tomography angiography (CTA). Moreover, the FFR derived from coronary CTA (FFRCT) Planner is a tool that simulates PCI providing modeled FFRCT values after stenosis opening. Aim To validate the accuracy of the FFRCT Planner in predicting FFR after PCI with invasive FFR as a reference sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“… 31 Our results highlight that ΔFFR CT can provide clinically relevant insight into the physiological pattern of disease requiring revascularization. With the emerging use of CCTA and FFR CT to guide PCI, 32 ΔFFR CT may provide further non-invasive guidance for optimizing revascularization strategies and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Our results highlight that ΔFFR CT can provide clinically relevant insight into the physiological pattern of disease requiring revascularization. With the emerging use of CCTA and FFR CT to guide PCI, 32 ΔFFR CT may provide further non-invasive guidance for optimizing revascularization strategies and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This substudy is a predefined analysis of the P3 (Precise PCI Plan), which study design and main results have been reported elsewhere. 10 , 11 Briefly, the P3 study was a prospective, investigator‐initiated, multicenter study of patients with stable CAD referred for PCI. Patients with a significant epicardial lesion based on an FFR ≤0.80 were considered for inclusion.…”
Section: Methodsmentioning
confidence: 99%
“…The authors reported that culprit lesions had worse haemodynamic parameters, and that detailed assessment with anatomical severity, adverse plaque characteristics, and axial plaque stress demonstrated discriminatory ability in identifying culprit lesions for subsequent ACS, compared with traditional anatomy-based models. In another study, Dey et al [ 39 ] investigated whether lesion-specific ischemia by invasive FFR could be predicted by an ML-based ischemia risk score derived from plaque measurement from CCTA, using a boosted ensemble algorithm. The authors found that the new ML-powered integrated ischemia risk score showed higher prediction of ischemia, when compared to traditional individual CCTA metrics such as plaque volume or pre-test likelihood of CAD [ 39 ].…”
Section: Coronary Ctmentioning
confidence: 99%
“…In another study, Dey et al [ 39 ] investigated whether lesion-specific ischemia by invasive FFR could be predicted by an ML-based ischemia risk score derived from plaque measurement from CCTA, using a boosted ensemble algorithm. The authors found that the new ML-powered integrated ischemia risk score showed higher prediction of ischemia, when compared to traditional individual CCTA metrics such as plaque volume or pre-test likelihood of CAD [ 39 ]. Finally, there is a growing interest in the use of CCTA and AI to guide clinical response following treatment such as PCI for significant lesions.…”
Section: Coronary Ctmentioning
confidence: 99%